2022
DOI: 10.1097/01.asw.0000820252.96869.8e
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Pyoderma Gangrenosum in Patients on Biologic Therapies: A Systematic Review

Abstract: OBJECTIVE:To summarize clinical outcomes of paradoxical pyoderma gangrenosum (PG) onset in patients on biologic therapy. METHODS:The authors conducted MEDLINE and EMBASE searches using PRISMA guidelines to include 57 patients (23 reports). RESULTS:Of the included patients, 71.9% (n = 41/57) noted PG onset after initiating rituximab, 21.1% (n = 12/57) noted tumor necrosis factor α (TNF-α) inhibitors, 5.3% (n = 3/57) reported interleukin 17A inhibitors, and 1.8% (n = 1/57) reported cytotoxic T-lymphocyte-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Conversely, a recent systematic review demonstrated that rituximab may be associated with the onset of vulvovaginal PG [ 137 ]. In fact, rituximab appears to be responsible for the majority of new-onset PG cases reported during biologic therapies [ 138 ].…”
Section: Biologicsmentioning
confidence: 99%
“…Conversely, a recent systematic review demonstrated that rituximab may be associated with the onset of vulvovaginal PG [ 137 ]. In fact, rituximab appears to be responsible for the majority of new-onset PG cases reported during biologic therapies [ 138 ].…”
Section: Biologicsmentioning
confidence: 99%
“…In an analysis of all case reports in which PG was thought to have been triggered by the administration of biological therapy, 57 patients were identified. Here, 41 cases involved rituximab, 12 cases involved TNF-α inhibitors, 3 cases involved interleukin 17A and one case involved cytotoxic T-lymphocyte-associated protein 4 antibodies [ 31 ]. It is hypothesised that in these paradoxical reactions, there is a shift of the cytokine balance towards a molecular pattern typical of the respective induced disease.…”
Section: Drug-induced Pyoderma Gangrenosummentioning
confidence: 99%